Recurrence of Left Ventricular Outflow Tract Obstruction Requiring Alcohol Septal Ablation after Transcatheter Aortic Valve Implantation - Hideki Kitahara; Kaoru Matsuura; Atsushi Sugiura; Akiko Yoshimura; Takahiro Muramatsu; Yusaku Tamura; Takashi Nakayama; Yoshihide Fujimoto; Goro Matsumiya; Yoshio Kobayashi (Case Reports in Cardiology)
Left ventricular outflow tract (LVOT) obstruction is sometimes observed in patients with severe aortic stenosis (AS). It is still controversial how to manage the remaining severe AS, when LVOT obstruction is well-controlled by medical therapy. We report a case with acute recurrence of LVOT obstruction requiring emergent alcohol septal ablation (ASA) after transcatheter aortic valve implantation (TAVI), even in a stable state on beta-blockers. For the ASA procedure, transesophageal echocardiography was useful to clearly observe the perfusion area of the target septal branch by injecting microbubble contrast. Since it took some time to cause the recurrence of LVOT obstruction in this case, careful evaluation should be done after TAVI in high-risk patients for LVOT obstruction before terminating the TAVI procedure.